2017
DOI: 10.1002/polb.24423
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oriented β‐lamellae on deformation and pore formation in β‐nucleated polypropylene

Abstract: Four β‐nucleated polypropylene samples with increasing die draw ratio (DDR) were prepared to modify lamellae arrangement. The DSC, SEM, and 2D‐XRD results show that all four cast films had similar crystallinity, high contents of β‐crystal but lowering stability of β‐lamellae with ascending DDR. Meanwhile, the anisotropy of β‐lamellae distribution strengthens gently and the stacked lamellae structure perpendicular to the machine direction (MD) predominates dramatically. Tensile testing at 25 °C and 90 °C were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
(126 reference statements)
0
12
0
Order By: Relevance
“…The porosity was defined as the volume content of pores within the membrane and was calculated on the basis of the following equation: 31,32 porosity=Vp/Vf=()VfVr/Vf …”
Section: Methodsmentioning
confidence: 99%
“…The porosity was defined as the volume content of pores within the membrane and was calculated on the basis of the following equation: 31,32 porosity=Vp/Vf=()VfVr/Vf …”
Section: Methodsmentioning
confidence: 99%
“…At present, the most commonly used commercial separators are made from polyolefin due to the low cost. Three classical industrial processes used to produce LIB separators are the dry process with uniaxial stretching, 21,22 the dry process with biaxial stretching 23–25 and the wet process 26,27 . All these processes include an extrusion step to make cast films and employ one or more orientation steps to impart porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [27] investigated the pore formation process of four kinds of precursor films with different supermolecular structures and found that the sample with well-developed spherulite structure was more conducive to form uniform pores after stretching. Moreover, Ding et al [28] prepared four samples with different distributions of β-lamellae and revealed that the sample with lamellae almost all perpendicular to the stretching direction had homogenous deformation. Zhu et al [29] found that the crystalline morphology changed from spherulites into βtranscrystals by adding ultrafine full-vulcanized powder rubber (EA-UFPR), and its loosely-packed lamellae facilitated the formation of micropores.…”
Section: Introductionmentioning
confidence: 99%